Analisis Sintagmatik dan Paradigmatik Ferdinand Dessausure Pada Qs. Al-á¸ŒuhÄ - Sari, Maula (MAGHZA, 2020)
Humans will always find and find good signs in the form of language, symbols, human behavior, and so on. All visible signs do not appear even without cause. It's just that it has some hidden purpose. Exploration of the study of the Koran is gradually increasing. Which is focused on Signifier and Signifie in Qs. Al-á¸ŒuhÄ, Syntagmatics, and Paradigmatics in Qs. Ad Dhuha This study is of a qualitative type that will trace the meaning in the verses in Qs. Al-á¸ŒuhÄ which has been mentioned in the Koran in the context of its meaning and mention. Every verse in Qs. Al-á¸ŒuhÄ gathered and began to look for the sign elements contained in the verse, and look for Significant and Sinifie in Qs. Al-á¸ŒuhÄ then looked for Synagmatics and Paradigmatics in Qs. Ad Dhuha The results of the research in this article indicate if the semiotic approach in Qs. Al-á¸ŒuhÄ has meaning as an effort in studying and interpreting the Koran by looking at the signs contained in this surah. Existing signs in Qs. Al-á¸ŒuhÄ is not only clearly seen, but explicitly contained in each of his words. The purpose of this study, is expected for mankind, especially in the field of academics, who is always eager to study the Koran. Ferdinand de Saussure's linguistic semiotics found that the meaning of the verses in Qs. Al-á¸ŒuhÄ can be examined with Signifier and Signifie and syntagmatic and paradigmatic.